Reemployment rates over the life course: Is there still hope after late career job loss? - Katharina Frosch (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
The labor market situation for elderly job searchers is more difficult than for their younger counterparts. To identify patterns in the reemployment of the elderly, we analyze the employment histories of about 113.000 male job searchers in West-Germany. The analysis is based on a hazard rate model with piecewise constant intensities. We focus on age-specific reemployment rates. Individual characteristics, labor market indicators as well as the influence of the previous employment history on reemployment are accounted for. As expected, reemployment rates decline with age. Between 1975 and 1995, the negative impact of age on reemployment chances increases significantly. The obsolescence of human capital seems to play a decisive role for reemployment, especially for engineering occupations: From age 50 on, the negative age effect is significantly stronger than for other occupations.
Keywords: J64; J24; J14; 330; late career job loss; reemployment; hazard rate models; elderly engineers